Telegram-Bot Applications in Drug Information Services and Pharmaceutical Counseling - Anggitha, Shelvia Lharas; Rahayu, Ngesti; Pribadi, Prasojo; Santoso, Setiyo Budi (Prosiding University Research Colloquium, 2022)
This article presents the development of a bot application to assist patients in obtaining drug information and counseling services from pharmacists. The draw.io network software was used to build a bot workflow. This study's findings include recommendations for bot workflows as well as examples of user interface designs.